PRODUÇÃO DE LÂMINAS E PAINEL COMPENSADO MULTILAMINADO COM MADEIRA DE Hovenia dulcis Thunberg (UVA-DO-JAPÃO) - Bednarczuk, Ezaquel (2015)
The study aimed to evaluate the quality of plywood multi laminated produced with sapwood and heartwood of Hovenia dulcis Thunberg, and in combination with Pinus elliottii, considering the effect of the use of different pressing pressures and the influence of the characteristics of the wood in the properties of the panels. The anatomical and physical characterization of sapwood and heartwood of Hovenia dulcis and physical characterization of the wood of pinus. Was also performed to determination the yield of the lamination and the classification of the quality of the blades. The panels were manufactured under three specific pressing pressures (9, 12 and 15 kgfcm?) and in six combinations of wood blades, using the heart and sapwood of Hovenia dulcis or in combination with wooden blades of Pinus elliottii, in order to evaluate their physical and mechanical properties, according to ABNT rules. Phenol-phormaldehyde resin was applied, 160 g/m² particle weight in simple line and 35% solid contents. Anatomical analysis showed that the wood of sapwood is more permeable than the heartwood of Hovenia dulcis. The woods of sapwood and heartwood of Hovenia dulcis did not show a statistically significant difference for basic density, but both had higher basic density that the wood of Pinus elliotti. The dimensional stability of wood of Hovenia dulcis and Pinus elliottii was equivalent. The average yield of lamination to the logs of Hovenia dulcis was less than that of pinus, with average of 55,56%, but provided blades containing with knots smaller diameters. The manufactured panels presented physical and mechanical properties according to patterns defined by ABIMCI (Mechanically Processed Wood Industry Brazilian Association). Pressing pressure influenced bulk density, swelling and swelling plus retrieval thickness panels, which increased proportionally to pressure rise, on the opposite to water absorbance. The panels produced with blades of Hovenia dulcis had a higher bulk density, stiffness and strength of the glue line and lower water absorption and moisture content in relation to panels produced with pinus.